Strengthening Inclusivity Through Multicultural Islamic Education in Secondary Schools: A Qualitative Literature Analysis - Umamah, Choirul; Sari, Diyan Retno; Imaduddin, M.; Ilyas, Ahmad; Abidin, Zaenal (Kirana Publisher (KNPub), 2025)
Islamic education at the secondary school level has a strategic role in shaping the character of students who are inclusive and able to appreciate diversity in a multicultural society. However, the integration of the values of multiculturalism and inclusivity in educational practice still faces various challenges, such as cultural resistance and limited understanding of teachers. This research aims to answer three problem formulations, namely: how the concepts of inclusivity and multiculturalism are integrated in Islamic education, strategies used to strengthen the value of inclusivity, and challenges and opportunities for its implementation. The method used is library research or literature study with a qualitative approach, analyzing various sources of literature, both national and international. The results of the study show that strengthening inclusivity in multicultural Islamic education can be done through the development of a curriculum that is responsive to diversity, teacher training, and the creation of a school environment that is supportive of the values of tolerance and ihtiram at-tanawwu' (respect for diversity). In conclusion, multicultural Islamic education in secondary schools has great potential in building an inclusive society, but continuous commitment from all parties is needed. The recommendation of this study is the need for synergy between the government, schools, and the community in implementing education oriented to inclusivity and at-ta'ayush as-silmi (peaceful life together).